Rapid Fluorescent Probe Detection of Magnesium Impurities in High-Purity Lithium Carbonate Brine Systems - Yan Li; Huaigang Cheng; Yueyue He; Jing Zhao (Molecules)
The magnesium impurities in lithium carbonate cannot be detected quickly in an aqueous environment. To solve this bottleneck problem, this study proposes a new method for the rapid detection of trace Mg2+ in lithium carbonate using a water-soluble fluorescent probe. A water-soluble fluorescent probe A was obtained by introducing hydroxyl groups on a fluorescent oxazole ring. After modification, the hydrogen bonding between the probe and water molecules increased by more than 62 times. Consequently, the energy loss of outward transfer of the fluorescent probe increased, resulting in weak fluorescence in saline systems. Mg2+ was captured by N on the oxazole ring and O on the phenolic hydroxyl group through a 1:1 coordination ratio within the probe structure. The hydrogen bonding attraction between the complex and water molecules increased 16 times. Additionally, the orbital energy gap was reduced from 2.817 to 0.383 eV. Meanwhile, the Mg2+ impeded the phototropic electron transfer effect process, resulting in enhanced fluorescence and completing this process within 3 to 10 s, with a detection limit of 6.06 μmol/L. This method can promote the real-time and rapid quality control of Mg2+ impurities in the refining and purification of lithium carbonate, as well as effectively reduce production costs.